EXAMINING FACE-THREATENING ACT OF JAPANESE ADVERB YATTO - Nandang Rachmat; Hiroko Otsuka (Universitas Ngudi Waluyo, 2021)
Abstract In intercultural communications, we can anticipate the occurrence of unintended face-threatening acts (FTA) which leads to miscommunication. This study discusses the possible FTA by the speaker who does not intend to threaten the interlocutor’s positive and negative face by using one of the Japanese temporal adverbs, yatto. This adverb expresses the speaker’s evaluative meaning, is achieved through various obstacles and the effect takes a long time to achieve. In addition, the word yatto also implies an achievement that is attained by either barely sufficient abilities or because of an immediate deadline. Therefore, when being used to talk about the interlocutor's or the other person’s action, it can threaten his/her face. It is necessary to clarify the possibility of threatening other people's positive and negative faces even though it is unintentional because Japanese teachers and learners are mostly unaware of it. Many of them associate the word yatto as akhirnya in Bahasa Indonesia or finally in English, which does not contain the speaker’s evaluative meaning. Accordingly, the subject of this study is to clarify the conditions of use when the word yatto becomes an FTA. To clarify the problem, this study uses descriptive and qualitative methods and employs the theory of politeness, especially the theory of face-threatening acts (FTA) by Brown and Levinson (1987). Inspired by Kamio (1990)’s notion of the territory of information, there are three types of the territory of information for the yatto adverb; (a) the information that falls to the territory of the speaker, (b) to both of the speaker’s and the interlocutor’s or the other person’s, and (c) to the interlocutor. As the main finding of the research, the factor causing FTA for positive and negative faces, namely FTA which occurs when the speaker talks about the action, falls to (c) the third territory. In the case of the benefactive -tekureru or -temorau forms used together, the meaning appreciating the actions of the interlocutor or the third person, it works as positive politeness to them as an agent. On the contrary, expressing thanks threaten the speaker's negative face.